Tandem mass spectrometry in screening for inborn errors of metabolism: comprehensive bibliometric analysis - Kononets, Victoria; Zharmakhanova, Gulmira; Balmagambetova, Saule; Syrlybayeva, Lyazzat; Berdesheva, Gulshara; Zhussupova, Zhanna; Tautanova, Aidana; Kurmambayev, Yergen (Frontiers in Pediatrics, 2025)
Tandem mass spectrometry (MS/MS) for detection of inborn errors of metabolism (IEM) is recognized as an ethical, safe, simple, and reliable screening test. Presented bibliometric analysis aims to describe the network structure of the scientific community in the study area at the level of countries, institutions, authors, papers, keywords, and sources; scientific productivity, directions, and collaboration efforts in a considered period (1991–2024, May). Using the PRISMA method, we conducted a systematic search for articles reporting using MS/MS to screen for inherited metabolic disorders and inborn errors of metabolism collected from the Web of Science Core Collection (WoSCC). A total of 677 articles out of 826, by 3,714 authors, published in 245 journals, with 21,193 citations in 11,295 citing articles, with an average citation of 31.3 per article, and an H-index of 69 were retrieved from the WoSCC. The research status of MS/MS in IEM screening was identified. The most relevant current research directions and future areas of interest were revealed: “selective screening for IEM,” “new treatments for IEM,” “new disorders considered for MS/MS testing,” “ethical issues associated with newborn screening,” “new technologies that may be used for newborn screening,” and “use of a combination of MS/MS and gene sequencing”.